PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR SISWA PADA MATERI TRIGONOMETRI KELAS XI MIPA 4 SMA NEGERI 1 AMBARAWA - Oktavian Rosa Abrianto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2019)
This research is observed to increase the result and motivate the students in learning mathematics in Grade XI MIPA 4 of Ambarawa Senior High School with topic trigonometry by using peer tutor method. This research is includes class act observed. The method that I used in this research is called Kurt Lewin with 4 steps, they are planning, action, observing, and reflection. The increasing result of the study and motivation to learn in learning mathematics with can see it by points and questionnaire scores. The result shows that the average learning outcomes in cycle 1 and cycle 2 were 73,55 and 86,67 respectively with the percentage of class completeness in the first cycle and the second cycle respectively 64% and 85%. As for the aspects of learning motivation by 52% based on this, it can be concluded that the applications of peer tutoring methods cam improve learning outcomes and learning motivation in the trigonometry material of students of Grade XI MIPA 4 of Ambarawa Senior High School.